Application of critical distance approach for fatigue assessment of welded and HFMI-treated steel joints. (January 2022) - Karakaş, Özler; Leitner, Martin; Tüzün, Nail
Highlights: Fatigue tests were performed on as-welded and HFMI treated steel welded joints. Critical distance approach was used in fatigue assessment. Critical distance for as-welded steel joints were calculated as a = 0.10 mm. Critical distance for HFMI treated steel joints were calculated as a = 0.20 mm. For HFMI treated joints, a = 0.15 mm was proposed instead for reliability. Abstract: High Frequency Mechanical Impact (HFMI) treatment offers a great opportunity to enhance the lightweight potential of welded structures using high strength steel materials. Focusing on the IIW Recommendations for the HFMI Treatment, a fatigue assessment based on the nominal, structural as well as notch stress approach is considered. Due to its sound applicability and proper assessment of the fatigue strength, the critical distance approach acts as a valuable concept in fatigue design, which has not been broadly studied in terms of HFMI-treated weld joints. Therefore, this paper deals with the application of the critical distance approach for welded mild and high-strength steel joints in both as-welded and HFMI-treated condition. Critical distance values were determined as a = 0.1 mm for as-welded specimens and a = 0.2 mm for HFMI treated specimens but for the sake of reliability, a = 0.15 mm have been proposed for HFMI treated welded joints.